2020
DOI: 10.17294/2330-0698.1730
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Work Index: A Novel Method for Assessment of Myocardial Function in South Asian Recreational Athletes

Abstract: We used a novel noninvasive method based on speckle-tracking echocardiography to evaluate myocardial performance in South Asian recreational athletes who completed a half marathon. Methods Transthoracic echocardiography was performed on 24 recreational athletes 48 hours before they took part in a half marathon (premarathon), within 2 hours of half marathon completion (postmarathon), and 72 hours after completion. Clinical, laboratory, and echocardiographic variables were collected. Speckle-tracking echocardiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Few studies evaluated strain behaviour during exercise stress echocardiography [14] and dobutamine stress echocardiography [15][16][17]. Recently, a novel myocardial work index was investigated in patients during exercise stress echocardiography [18,19,20], and in athletes after a half marathon [21]. Results of our study showed that despite improvement in global strain, all the parameters of myocardial work deteriorated during dobutamine stress echocardiography: global work index, global constructive work, global work e cacy, and global wasted work.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Few studies evaluated strain behaviour during exercise stress echocardiography [14] and dobutamine stress echocardiography [15][16][17]. Recently, a novel myocardial work index was investigated in patients during exercise stress echocardiography [18,19,20], and in athletes after a half marathon [21]. Results of our study showed that despite improvement in global strain, all the parameters of myocardial work deteriorated during dobutamine stress echocardiography: global work index, global constructive work, global work e cacy, and global wasted work.…”
Section: Discussionmentioning
confidence: 75%
“…Results of our study showed that despite improvement in global strain, all the parameters of myocardial work deteriorated during dobutamine stress echocardiography: global work index, global constructive work, global work e cacy, and global wasted work. During normal exercise stress echocardiography, deterioration was found only in global wasted work [19] and global work e cacy [19,21]; the global work index improved [19,21] and global constructive work improved [19], Table 3. Our results show that the cardiac in uence of dobutamine is different from the effect of exercise during stress echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies evaluated strain during exercise stress echocardiography 20 and dobutamine stress echocardiography 5 , 17 23 . A novel myocardial work index was investigated in patients during exercise stress echocardiography 24 26 , and in athletes after a half marathon 27 . During normal exercise stress echocardiography, deterioration was found only in global wasted work 25 and global work efficacy 25 , 27 ; the global work index improved 25 , 27 and global constructive work improved 25 .…”
Section: Discussionmentioning
confidence: 99%
“…A novel myocardial work index was investigated in patients during exercise stress echocardiography 24 26 , and in athletes after a half marathon 27 . During normal exercise stress echocardiography, deterioration was found only in global wasted work 25 and global work efficacy 25 , 27 ; the global work index improved 25 , 27 and global constructive work improved 25 . In one study 26 , myocardial work index parameters were compared in normal versus ischemic response.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GWE at rest is able to predict functional capacity and pulmonary or hemodynamic congestion measured at peak effort, better than LVEF. Evaluation of MW indices in 24 half-marathon runners before, immediately post, and 72 hours after a marathon confirmed that GWE and GWW do not change significantly after the competition, but an increase in GWI has been observed in a subgroup of athletes with higher BNP values and higher heart rate [ 60 ]. Authors suggested that increased value of GWI post-marathon would reflect an early manifestation of myocardial stress with increased heart rate, which may be a precursor to myocardial fatigue.…”
Section: Clinical Applicationsmentioning
confidence: 99%